Results of a survey in Germany, Austria, and Switzerland on how to prevent violations of competition laws - Götz, Georg; Herold, Daniel; Paha, Johannes (Springer International Publishing, 2016)
This report presents the results of a survey on competition law compliance in Germany, Austria, and Switzerland in which 86 large companies participated. The study shows that 80% of the firms have implemented measures to identify and mitigate the risks of violating competition laws. The majority of firms and measures concentrate on legal risks (e.g. insufficient awareness of the content and scope of competition laws), whereas risks related to changes in the economic environment (e.g. entry into the market, competition by imports, and more intense competition) are rarely addressed. Risk mitigation heavily relies on competition law training, even though these measures hardly seem sufficient. This is obvious from the fact that 71% of the firms whose employees had violated competition laws in the past had already trained these employees before the misconduct occurred. We conclude from our study that those measures should be improved that help to detect cartelisation risks at an early stage. Furthermore, sanctions imposed by the firms on the offenders of competition laws require a clearer design and more systematic communication.
CRIS-Team Scopus Importer:2022-11-17